Impact of Bead-Beating Intensity on the Genus- and Species-Level Characterization of the Gut Microbiome Using Amplicon and Complete 16S rRNA Gene Sequencing - Zhang, Bo; Brock, Matthew; Arana, Carlos; Dende, Chaitanya; van Oers, Nicolai Stanislas; Hooper, Lora V.; Raj, Prithvi (Frontiers in Cellular and Infection Microbiology, 2021)
Bead-beating within DNA extraction protocol is critical for complete microbial cell lysis and accurate assessment of abundance and composition of microbiome. While the impact of bead-beating on the recovery of OTUs at the phylum and class level have been studied, its influence on species level microbiome recovery is not clear. Recent advances in sequencing technology allow species level resolution of the microbiome using full length 16S rRNA gene sequencing instead of smaller amplicons that only capture a few hypervariable regions of the gene. We sequenced v3-v4 hypervariable region as well as full length 16S rRNA gene in mouse and human stool samples and discovered major clusters of gut bacteria that exhibit different level of sensitivity to bead-beating treatment. Full length 16S rRNA gene sequencing unraveled vast species diversity in mouse and human gut microbiome and enabled characterization of several un-classified OTUs in amplicon data. Many species of major gut commensals such as Bacteroides, Lactobacillus, Blautia, Clostridium, Escherichia, Roseburia, Helicobacter and Ruminococcus were identified. Interestingly, v3-v4 amplicon data classified about 50% of Ruminococcus reads as Ruminococcus gnavus species which showed maximum abundance in 9 minute beaten sample. But remaining 50% reads could not be assigned any species. Full length 16S rRNA gene sequencing data showed that majority of the unclassified reads were Ruminococcus albus species which unlike R. gnavus show maximum recovery in the un-beaten sample instead. Furthermore, we found that Blautia hominis and Streptococcus parasanguinis species were differently sensitive to bead-beating treatment than rest of the species in these genera. Thus, present study demonstrates species level variations in sensitivity to bead-beating treatment that could only be resolved with full length 16S rRNA sequencing. This study identifies species of common gut commensals and potential pathogens that require minimum (0-1minute) or extensive (4-9 minute) bead-beating for their maximal recovery.